2020
DOI: 10.30547/worldofmedia.1.2020.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent news frames in news reports about military operations against Boko Haram in North-East Nigeria

Abstract: The media have been accused of bias against the military by framing Boko Haram group as being superior thereby making better-armed soldiers afraid of confronting the group in open battle. This accusation was without any empirical underpinning, thus this study objectives were to identify the framing patterns used by Nigerian newspapers in the coverage of military operations against the Boko Haram group in NorthEast Nigeria. Four national dailies, Daily Trust, Premium Times, The Nation and Vanguard, were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Okoro and Odoemelam (2013) agreed that the type of frames examined in a media content analysis is determined by the nature of the subject being investigated. Ndinojuo, Ihejirika and Okon (2019) also confirmed that there is no unitary classification of frames; however, what determines framing patterns for each study depends on research objectives. Therefore, the essential consideration in frame selection is the purpose of the research endeavour.…”
Section: Frames Used In Reporting Terrorismmentioning
confidence: 74%
See 1 more Smart Citation
“…Okoro and Odoemelam (2013) agreed that the type of frames examined in a media content analysis is determined by the nature of the subject being investigated. Ndinojuo, Ihejirika and Okon (2019) also confirmed that there is no unitary classification of frames; however, what determines framing patterns for each study depends on research objectives. Therefore, the essential consideration in frame selection is the purpose of the research endeavour.…”
Section: Frames Used In Reporting Terrorismmentioning
confidence: 74%
“…In a study, "Television webcast framing of the Nigerian government's response to Boko Haram insurgency in North-East Nigeria," Chioma and Ojomo (2015) used conflict frame, human interest frame, economic consequence frame, critical and distance frames. In another study, Ndinojuo et al (2019) 2013) adopted the following frames: response frame, political frame, economic frame, religious frame, and ethnic frames. Similarly, Semetko and Valkenburg (2000), Iyengar (1994) and De Vreese (2005) developed the following frames: powerlessness frame attribution of responsibility frame, labeling frame, human interest frame and conspiracy frame.…”
Section: Frames Used In Reporting Terrorismmentioning
confidence: 99%
“…Thus, the media can be seen as agents acting in the interests of certain beneficiaries, and various biases or distortions observed in the content do not stem from the commitment of journalists to different political ideologies, but result from the fact that media could be used to control the political narrative. Under certain circumstances, using a specific set of rhetorical and expressive means, the media turn into initiators of conflict, intentionally portraying some events as conflicts, using the so-called frame of the conflict (Ndinojuo et al, 2020).…”
mentioning
confidence: 99%